Memahami Dimensi Keibuan dan Keperawanan dalam Dokumen Mulieris Dignitatem No. 17-21 - Merina Ndruru; Megawati Naibaho; Mawarni Gea (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
God created human being in His Image and endowed them with the holy dignity. The women has a special call to be a mother. This vocation united with noble aspects of motherhood and virginity. The understanding of motherhood and virginity is sometimes not appreciated as a special gift. Consequently, the vocation of motherhood is marked by discrimination and violence against women. The aim of writing this research is to explore the noble aspects of women as motherhood and the virginity. This will open new understanding and awareness to respect women on their vocation as a mother or a nun. To explore this research, the researcher uses library research method. The researcher collects various sources and analyzes them systematically. The researcher explores aspects of motherhood and virginity and relates it to the figure of Mary both mother and virgin. These two dimensions unite in the person of Mary who was chosen by God to be the mother of Jesus. To explain aspects of motherhood and virginity, the researcher explores the document Mulieris Dignitatem. Women as the image of God have the privilege of motherhood and virginity like Mary. This dimensions of Mary are important spirituality on this present time. The implication of this research will open new understanding and awareness on dimension of motherhood and virginity which often underappreciated and abused. This research aim will empower the spirit of the dimensions of motherhood and virginity as the dignity of women and measured of image of God.